Association between TORCH infection and lupus anticoagulant antibody in pregnant women with recurrent abortion: TORCH infection and lupus anticoagulant antibody in pregnant women - Fatah, Hiwa R. (Cellular and Molecular Biology, 2023)
Abortion is a medical condition that describes pregnancy loss due to various causes including TORCH infections (toxoplasmosis, others (syphilis and hepatitis B), rubella, cytomegalovirus (CMV), and herpes simplex virus (HSV) infection). TORCH infections may pass to the fetus that has low immunity to fight the disease, besides; the complications are much higher during the early stages of pregnancy which may involve abortion. Therefore, investigating the possible factors that could be associated with TORCH infection including the clotting factor lupus anticoagulant antibody is vital. In this study, TORCH antibodies in 33 pregnant women were assessed and then lupus anticoagulant antibodies were tested using Diagnostica Stago STart 4 Hemostasis Analyzer. The serum concentration of immunoglobulin M (IgM) and immunoglobulin G (IgG) for toxoplasma, rubella and CMV were quantitatively determined with Cobas e411. The serum concentration of IgG for rubella and CMV increased in the blood were 90.9% and 66.6% of pregnant women respectively, while toxoplasma results showed an increasing level of IgG in 24.4% of patients. IgM levels for toxoplasma, rubella and CMV are elevated in 6.1%, 3.03% and 24.2% of patients respectively. Lupus anticoagulant antibody is increased in the blood of 72.7% of pregnant women. It was concluded that only rubella and CMV infections cause the increase of lupus anticoagulant antibodies in the tested pregnant women, not toxoplasmosis.